ANALISIS FAKTOR PERAMALAN MEREK TERHADAP LOYALITAS MEREK (Kasus pada sabun deterjen Rinso di Kota Makassar) - Sumarni Sumarni (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2011)
This research aim to learn by empiric is influence from brand predictability, have an effecton the signifikan to brand loyality. The brand under analysis was Rinso detergent soap. The respondents were the consumers of Rinso deterjent soap brand in Makassar . The whole test of hypothesis was carried out using multiple linear regression analysis mathematical model. The results show thant brand predictability (X1), by togheter have an effect on the signifikan to brand loyality (Y). Level of the influence shown by level of coefficient determinasi that equal to R²=58,00%, meaning 58,00% cause of change of loyalitas brand (Y) is change with that happened at brand predictability (X1)). While 42% the rest of because of other; dissimilar variabel is which not covered in model.